Feeding regime effect of life feed on the growth and survival of angelfish postlarvae (Pterophyllum scalare) - Fitri, Megana; Nuraini, Nuraini; Heltonika, Benny (Universitas Malikussaleh, 2025)
Angelfish is economically of ornamental fish, but slow growth on post larvae phase is problem for this fish. Once solution for this problem is to find optimal feed to support and accelerate the growth of angelfish larvae by providing appropriate feed for life feed types. The research was conducted from March to May 2023 at the Fish Breeding and Genetics Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau. The objective of this study was to investigate the influence of feeding regime of life feed to angelfish larvae (Pterophyllum scalare). The research using a Completely Randomized Design (CRD) with one factor, consisting of 5 treatment levels and 3 replications. The treatments used P1 (Artemia sp for 2 weeks + Tubifex for 4 weeks), P2 (Mosquito larvae for 2 weeks + Tubifex for 4 weeks), P3 (Infusoria for 2 weeks + Tubifex for 4 weeks), P4 (Tubifex for 6 weeks), and P5 (Artemia sp for 6 weeks). The larvae were reared for 42 days with a stocking density of 3 fishes/L. The results showed that substituting natural feed with different types had a significant effect, particularly in treatment P2 which resulted in an absolute weight growth of 2.46 g, absolute length growth of 4.01 cm, specific growth rate of 14.53%, and larval survival rate of 88.15%. The water quality during the study was within the normal. The temperature ranged from 27.6 to 28.5 ºC, pH ranged from 6.0 to 8.0, and dissolved oxygen (DO) ranged from 4.5 to 5.3 mg/L.Keywords: Artemia sp; Decorative fish, Infusoria; Silk worm